2018
DOI: 10.1038/s41467-018-05839-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a turbulent ExB mixing avalanche mechanism of gas breakdown in strongly magnetized systems

Abstract: Although gas breakdown phenomena have been intensively studied over 100 years, the breakdown mechanism in a strongly magnetized system, such as tokamak, has been still obscured due to complex electromagnetic topologies. There has been a widespread misconception that the conventional breakdown model of the unmagnetized system can be directly applied to the strongly magnetized system. However, we found clear evidence that existing theories cannot explain the experimental results. Here, we demonstrate the underly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 40 publications
1
39
0
Order By: Relevance
“…Close to the wall, there are hot plasma zones directly linked to the magnetic separatrices (see fig. 10 of [33]). Because of the low density, the plasma interacts strongly with the walls, by means of ExB drifts and secondarily of open magnetic field lines [33].…”
Section: Traditional Ohmic Start-up Of the Tokamakmentioning
confidence: 98%
See 1 more Smart Citation
“…Close to the wall, there are hot plasma zones directly linked to the magnetic separatrices (see fig. 10 of [33]). Because of the low density, the plasma interacts strongly with the walls, by means of ExB drifts and secondarily of open magnetic field lines [33].…”
Section: Traditional Ohmic Start-up Of the Tokamakmentioning
confidence: 98%
“…10 of [33]). Because of the low density, the plasma interacts strongly with the walls, by means of ExB drifts and secondarily of open magnetic field lines [33]. This direct interaction with the walls lasts till the formation of closed magnetic surfaces and produces a lot of impurities, in particular during the burn-through phase.…”
Section: Traditional Ohmic Start-up Of the Tokamakmentioning
confidence: 98%
“…This implies the reduction of turbulence persisting in the plasma from the breakdown 79 . As the ITB location expands to , the uctuation is severely reduced implying stabilisation of turbulence.…”
Section: Analysis Of Core Itb Characteristicsmentioning
confidence: 99%
“…2018; Yoo et al. 2018). It has been found that the self-electric field produced by charge separation plays a large role in plasma breakdown.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental studies (Sand, Waelbroeck & Waidmann 1973;Holly et al 1981;Lloyd & Edlington 1986;Yoshino & Seki 1997;Kajiwara et al 2005) revealed that the electric field can be smaller when using the assist heating or preionization methods. In recent decades, many further studies have been developed on plasma breakdown (Jiang et al 2016;Yoo et al 2017;Peng et al 2018;Yoo et al 2018). It has been found that the self-electric field produced by charge separation plays a large role in plasma breakdown.…”
Section: Introductionmentioning
confidence: 99%